Diffusion of Antimicrobials Across Silicone Hydrogel Contact Lenses. Issue 5 (September 2015) - Zambelli, Alison M.; Brothers, Kimberly M.; Hunt, Kristin M.; Romanowski, Eric G.; Nau, Amy C.; Dhaliwal, Deepinder K.; Shanks, Robert M. Q.
Abstract : Objectives: To measure the diffusion of topical preparations of moxifloxacin, amphotericin B (AmB), and polyhexamethylene biguanide (PHMB) through silicone hydrogel (SH) contact lenses (CLs) in vitro. Methods: Using an in vitro model, the diffusion of three antimicrobials through SH CLs was measured. Diffused compounds were measured using a spectrophotometer at set time points over a period of 4 hr. The amount of each diffused antimicrobial was determined by comparing the experimental value with a standard curve. A biological assay was performed to validate the CL diffusion assay by testing antimicrobial activity of diffused material against lawns of susceptible bacteria ( Staphylococcus epidermidis ) and yeast ( Saccharomyces cerevisiae ). Experiments were repeated at least two times with a total of at least four independent replicates. Results: Our data show detectable moxifloxacin and PHMB diffusion through SH CLs at 30 min, whereas AmB diffusion remained below the limit of detection within the 4-hr experimental period. In the biological assay, diffused moxifloxacin demonstrated microbial killing starting at 20 min on bacterial lawns, whereas PHMB and AmB failed to demonstrate killing on microbial lawns over the course of the 60-min experiment. Conclusions: In vitro diffusion assays demonstrate limited penetration of certain anti-infective agents through SH CLs. Further studies regarding the clinical benefit of using these agents along with bandage CL for corneal pathologic condition are warranted.